PENGARUH FINANCIAL DISTRESS, AUDIT STENURE, DAN KOMISARIS INDEPENDEN TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2023 - Fuji Lestari; Hernadianto Hernadianto; Ahmad Sumarlan; Nensi Yuniarti (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This research aims to determine the effect of Financial Distress, Audit Tenure, and Independent Commissioners on the Integrity of Financial Reports with Audit Quality as a Moderating Variable in LQ 45 companies listed on the IDX (2020-2023). The population in this study consisted of 45 companies. The sampling technique selected based on certain criteria using purposive sampling was 25 samples. This research is a quantitative study with secondary data. The method used is a quantitative method processed with the SPSS 30 application. The techniques and data analysis used are descriptive statistics, classical assumption tests, multiple regression analysis and moderation regression analysis. The results of this study indicate that the financial distress variable affects the integrity of financial reports, audit tenure and independent commissioners do not affect the integrity of financial reports. Furthermore, audit quality moderation is unable to moderate the relationship between financial distress, audit tenure and independent commissioners on the integrity of financial reports. Keywords: Financial Distress, Audit Tenure, Independent Commissioner, Financial Report Integrity and Audit Quality